Estimates of cancer burden in Liguria. Issue 3 (May 2013) - Vercelli, Marina; Quaglia, Alberto; Lillini, Roberto; Rossi, Silvia; Foschi, Roberto
Aims and background: The regional health care system of Liguria caters for a resident population which is among the oldest in Europe. One population-based cancer registry is present in the region, providing incidence and survival data for the Genoa province (covering 55% of the regional population). This paper will estimate the incidence, prevalence and mortality in the Liguria region for cancers of the lung, breast, prostate, colon-rectum, stomach and uterine cervix and melanoma of the skin in 1970—2015. Methods: The estimated figures were obtained by applying the MIAMOD method. Starting from mortality and survival data, incidence and prevalence were derived using a statistical back-calculation approach. Survival was modeled on the basis of published data from the Italian cancer registries. The MIAMOD method was applied also to estimate the colorectal cancer incidence, mortality and prevalence rates in the Ligurian provinces in the period 1988—2015. Results: In 2012 about 1, 500 new cases of breast cancer were expected in Ligurian women. The estimates for the other cancer sites were considerably lower, ranging from 839 (colon-rectum) to 54 (cervix). In men about 1, 400 new cases were estimated for prostate cancer, while the incidence for the other sites ranged from 1, 118 (colon-rectum) to 208 (skin melanoma). The breast cancer prevalence rate was more than 10 times the incidence rate in women, and the lung cancer prevalence rate was more than double the incidence rate in both sexes. Mortality rates were highest for lung cancer in men and breast cancer in women; the lowest rates were estimated for melanoma and cancer of the uterine cervix. Conclusion: In Liguria a large portion of the health expenditure has been devoted to diagnostic and therapeutic resources. This may have contributed to the reduction of mortality rates and to the improvement of cancer survival. This phenomenon, added to population aging, will inflate the cancer prevalence. One of the major challenges for the Liguria region is to face the increasing demand for oncology services.